Time of guard of orthodontic records versus legal time for their prescription - Luiz Renato Paranhos; Mariana Paula Maggiorini de Magalhães; José Francio; Hélio Hissashi Terada; Henrique Damian Rosário; Rhonan Ferreira da Silva (Dental Press Editora, 2013)
INTRODUCTION: After promulgation and wider dissemination of the Code of Consumer Protection, there was an increase in the number of legal conflicts between patients and dentists, leading these health professionals to increasingly guard themselves from possible lawsuits. As such, it becomes critical the preparation of an adequate and complete clinical record, even though the keeping time remains uncertain. OBJECTIVE: To review the literature and discuss the keeping time of orthodontic records versus the legal time for their prescription, as well as to propose a model of a Term upon Completion of Dental Treatment. CONCLUSION: It is advised to return part of the clinical records to their rightful owners by means of an itemized receipt. The Term upon Completion reflects the patient's awareness and could be considered by the CCP as the initial term of the prescription time, because it implicates that the patient recognizes the quality of service provided and satisfactory results achieved.